2001
DOI: 10.1097/00005176-200108000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Migraine in Children With Neurofibromatosis Type 1: A Case Series and Review of Gastrointestinal Involvement in NF1

Abstract: Abdominal pain secondary to migraine is an unrecognized cause of abdominal pain in children with NF1 and may be more common than anatomic causes of abdominal pain in children with NF1. In children with NF1 and severe recurrent abdominal pain in whom an evaluation for anatomic lesions is negative, a trial of migraine therapy may be indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…35 The latter 2 disorders have significant associations with inherited syndromes, namely, Cowden syndrome (ganglioneuromatous polyposis), 16,21,34 and MEN 2B or NF1 (ganglioneuromatosis). 6,12,15,29,33,35 As none of the patients in this study had more than 1 neural polyp at the time of evaluation of the index polyp, or upon follow-up, these disorders would not be diagnostic considerations. Solitary polypoid ganglioneuromas are the most common form of colorectal ganglioneuromas and are sporadic, not associated with inherited syndromes.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…35 The latter 2 disorders have significant associations with inherited syndromes, namely, Cowden syndrome (ganglioneuromatous polyposis), 16,21,34 and MEN 2B or NF1 (ganglioneuromatosis). 6,12,15,29,33,35 As none of the patients in this study had more than 1 neural polyp at the time of evaluation of the index polyp, or upon follow-up, these disorders would not be diagnostic considerations. Solitary polypoid ganglioneuromas are the most common form of colorectal ganglioneuromas and are sporadic, not associated with inherited syndromes.…”
Section: Discussionmentioning
confidence: 91%
“…11,33,36 In contrast, involvement of the gastrointestinal (GI) tract is rare. Neural lesions of the colon are a heterogeneous group of disorders, which may present as masses (such as schwannomas and neurofibromas), 7,15,17,25,30,32 or, more commonly, as small colorectal polyps. The latter seem to be detected with increasing frequency, as colonoscopic screening for colorectal cancer becomes more widely used.…”
mentioning
confidence: 99%
“…In a previous pilot study, we found that children with NF1 had abnormally large rectal diameters and a higher proportion than expected had prolonged colonic transit time [6]. A retrospective assessment of 126 children concluded that an abdominal migraine could be a significant cause of abdominal pain in children with NF1 [7]. For the present study, we hypothesized that adult patients with NF1 have an increased prevalence of gastrointestinal symptoms.…”
Section: Introductionmentioning
confidence: 77%
“…Abdominal migraine has been reported as a cause of episodic abdominal pain in children with NF1 and may be more common than anatomic causes of abdominal pain. 68 Treatment with migraine medications, such as propranolol and cyproheptadine, can be helpful. Plexiform neurofibromas involving the mesentery or retroperitoneum are only rarely a source of abdominal pain, vomiting, and abdominal mass.…”
Section: Gastrointestinalmentioning
confidence: 99%